KONSEP TAWAKAL DAN RELEVANSINYA DENGAN TUJUAN PENDIDIKAN ISLAM: Studi Komparasi mengenai Konsep Tawakal menurut M. Quraish Shihab dan Yunan Nasution - Abdul Ghoni (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2016)
Trust is the submission of all things, effort, and efforts made to God and to be surrender completely to Him to get the benefit or refuse kemudaratan. Formulation of the problem this discussion is how the concept of trust by M. Quraish Shihab and M. Yunan Nasution? How relevant concept of trust by M. Quraish Shihab and M. Yunan Nasution with the educational goals of Islam? Discussion of the results showed that under the concept of Quraish Shihab, trust does not mean absolute submission to God, but the handover must be preceded by human effort. According to the concept of Yunan Nasutian if every effort has been made, then surrendered (trust) in God, and trust and even then may not completely stop the effort or endeavor. The trust without effort, and effort it is not surrender his name, but gave up. The teachings of Islam put the effort or the business as a major factor, so that after the worshipers who are required to get back to their jobs, endeavors seeking sustenance. Expert second opinion when compared (Quraish Shihab and Yunan Nasution), then the equation, the two figures assume trust must be preceded by maximum effort or endeavor, afterward resignation. Differences concept of these two characters, namely Quraish Shihab tend to approach Tafsir al-Qur'an, while Yunan Nasution leads to propaganda approach. The concept of trust relationships by Quraish Shihab and Yunan Nasution with the goal of Islamic education as follows: Islamic educational goals is the creation of the perfect man in it have insight as true (full / full / complete). Last Interest Islamic education is surrender completely to God. "The word surrender completely to God" in religious language is called trust. Islamic educational purposes as this is also in line with the First World Conference on Islamic Education (1977) concluded that the ultimate goal of Islamic education is a human who give themselves absolutely to God.